The regulatory capital and Liquidity Management impact on Profitability of Commercial Banks in Lesotho. - Moshoeshoe, Mphaphathi (My University, 2019)
ABSTRACT The objective of this research is to assess the impact of the Basel III regarding Capital and Liquidity regulations on the profitability of commercial Banks in Lesotho using panel data of 3 banks from 2007 to 2017. The Bank profitability is measured by Return on Assets (ROA) and Return on Equity (ROE). The variables affecting bank profitability were categorised into Basel regulation variables, Bank-specific variables, industry-specific and macroeconomic variables. The Basel regulations variables are Common Tier 1 Capital Ratio (CET 1), Liquidity Coverage Ratio (LCR) and Net Stable funding ratio (NSFR), and these three variables are the main focus of this study. The bank-specific variables are cost-to-income ratio, Loan-to-Deposit ratio, and interest rate spread. The macro-economic variables are Real Growth Domestic Product (GDP), Consumer Product Index (CPI) and an Unemployment Rate and the industry-specific is the Herfindahl-Hirschman Index. The estimation techniques applied in the study were Fixed Effects, Pooled Ordinary Least Square (OLS), Random Effect. The findings revealed that of the Basel III regulatory variables, CET 1 significantly negatively affects ROE. This means that building the capital buffer to meet regulations will reduce the return on equity; notwithstanding, commercial banks in Lesotho are were well capitalised, and researchers have shown that the process of accumulating capital reduces the return on equity in the short-run, with improvements in profitability in the longer run. The liquidity regulations LCR and NSFR do not appear to have a significant impact given the data in the sample, however, that does not reduce their relevance to the banking sector in Lesotho and considering the nature and of banking in Lesotho, where there no active market and lesser completed products structures the impact might be minimal. Bank specific variables of cost income ratio (CIR) and loan to deposit (LTD) are in line with available literature on the topic of bank profitability and are shown to be the variables with the strongest impact on profitability measures of ROE and ROA. An increasing CIR negatively impacts profitability and increasing LTD positively impacts profitability. Of the macro variables, inflation is only mildly significant The research is a contribution to the studies on Basel III and its impact on profitability specifically in developing countries. The Lesotho Banking sector and regulator will benefit from the findings and enable them to assess the impact for Basel III future implementation. In addition, the research confirms the findings of existing literature that cost income and loan to deposit ratios have a significant impact on profitability.
Keywords: Basel capital, liquidity requirements, profitability, ROE, ROA